BURNOUT NORTH OF 60: AN INVESTIGATION OF TURNOVER AND BURNOUT AMONGST SOCIAL WORKERS IN NUNAVUT AND HOW TO BETTER SUPPORT THEM - McKenzie, Cameron S. (My University, 2012)
This qualitative study examines variables that can impact job stress, burnout, and turnover rates among social workers north of 60. The research herein seeks to fill in some gaps surrounding research on service worker employment conditions in the north that has not been specific to social workers serving Inuit clients. While the provisional literature review highlights possible conditions such as: social and geographical isolation, role stress, personality factors, and cultural and ethnic disparities as possible sources of burnout, these have never been evaluated in a manner specific to northern social workers. In-depth, semistructured interviews were conducted via telephone with nine former Nunavut social workers and directors in order to probe the issue of burnout and turnover. Application of Interpretive Social Sciences (ISS) and hermeneutical phenomenological approaches (HPA) to interview analysis revealed a trend in themes related to the administration of northern social work services, including: understaffing, lack of supervisory support, dual role stress, and overworked staff who already face the challenges of cultural incongruence for which they have been insufficiently trained to deal with. Final recommendations include increased attention and resources to the social work staff supporting vulnerable Inuit clients, including increased staffing and culturally sensitive training.
Keywords: North; Nunavut; Social Work; Stress; Burnout; Turnover; Human Geography; Public Health and Community Nursing; Public Policy; Social Policy; Social Welfare; Social Work; Human Geography